A Study on the knowledge and practice of health care waste management in Dang District. - Paudel, Raj Kumar (2012)
SUMMARY: Health care waste management is an important aspect of solid waste management. Health care waste should be treated separately and should be given due priority over all other forms of wastes. The haphazard collection, transportation and disposal of health care waste not only make the environment unsightly but also attribute harmful effect in human health. Government hospitals in Nepal are not untouched by this problem. In this context the study was carried out with the objective to find out and compare the current health care waste management practice in public hospitals of Dang, District. A descriptive, cross sectional and comparative study was conducted in Rapti Sub-Regional Hospital and Rapti Zonal Hospital, Dang. The study site was selected purposively. Primary data were collected through interview, group discussion, and observation. From the study it was found that there was not a vast public health care institutions regarding hospital waste management. Waste segregation was not in practice in both health care institutions at the point of generation though at the time of disposal they were separated as degradable and non degradable waste in Rapti Sub-Regional Hospital and Rapti Zonal Hospital. Both health institutions had used safety boxes for the collection of syringes and needles. Manual transportation was in practice and all the containers used for collection were uncovered in both institutions. Haphazard treatment and disposal of the health care waste was one of the burning issues. Open burning, simple burial and haphazard dumping were the usual practices of the health care institutions. Occupational health and safety was not given due attention. The sweepers were not given any training regarding hospital waste management nor were provided with protective measures like boots, cap and apron. Soap and water were used for hand washing purpose after handling wastes. All most all sweepers were alert of diseases that can be caused from hospital waste three of them were injured while handling waste. Only two of the sweepers had taken the vaccination against Hepatitis-B. General people visiting both health care institutions had sound knowledge on diseases that can be caused from hospital waste but most of them (60%) thought that all waste handlers and cleaners were responsible for hospital waste management. Though general public had sound knowledge on diseases caused from health care waste but had no idea on proper use of different color coded buckets. Thus it is necessary to maintain well and attractive labeling on different colored buckets for proper collection of wastes by general people visiting health care institutions. Hence it is found necessary that health care institutions need to develop their own document for hospital waste management or they need to follow national guidelines. They should also establish waste management committee and policies regarding health care waste management. Health care institutions should provide training and orientation classes to all from time to time regarding health care waste management for the betterment of institutions, all staffs, patients and to increase the efficacy of all workers.